Asupan Makanan dan Kadar Kolesterol Total Terhadap Kadar Gula Darah Wanita Dewasa di Kota Bengkulu - Kusdalinah Kusdalinah; Desri Suryani; Anang Wahyudi (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Diabetes mellitus is a chronic metabolic disease known as the silent killer and the parent of hypertension, heart and blood vessel disease, stroke, kidney failure, and blindness. The purpose of this study was to determine the relationship between food intake, cholesterol levels and blood sugar levels in Bengkulu City. Analytical observational research design with a cross sectional approach. The research was carried out in the working area of the Telaga Dewa Health Center, Bengkulu City. The time of the study was carried out in August–November 2020. The study population was adult women aged 25-65 years. Sampling by random sampling with cluster sampling method amounted to 125 people. Univariate and bivariate data analysis with Spearman correlation test. The results showed that the average age of the respondents was 44 years, the average body mass index was 25.6, the median fasting blood sugar level of 90 was at least 51 and the maximum was 357, food intake (carbohydrates, fiber) was still below the nutritional adequacy rate and the median cholesterol level. 194 mg/dl minimum 106 and maximum 104. There is no relationship between food intake, cholesterol levels and blood sugar levels. There is a relationship between age and fasting blood sugar levels of adult women in Bengkulu City.